Transformasi Industri Halal di Era Digital: Inovasi Menuju Pertumbuhan Ekonomi Indonesia 4.0 - Hamdan Fathurrahman; Atmo Prawiro (STAI Al-Mas'udiyah, 2025)
This article analyzes the role of innovation and digitalization in accelerating the growth of the halal industry in Indonesia through normative and literature-based approaches, as well as an interdisciplinary review from the perspectives of Islamic economics, information technology, and consumer behavior. The study's results indicate that the integration of technology in halal businesses can drive efficiency, expand market access, and enhance financial inclusion. Nonetheless, challenges such as limited digital infrastructure and low technology literacy among halal MSME players remain significant barriers. With regulatory strengthening through Law Number 33 of 2014 and support from institutions such as the National Committee for Sharia Finance (KNKS), Indonesia is expected to accelerate the halal industry roadmap and become a key player in the global market.